Rancang Bangun Aplikasi Validator Tagihan Pada Kantor Pelayanan Perbendaharaan Negara Kota Palopo - Muh Khaifun; Nirsal (Ikatan Ahli Informatika Indonesia, 2024)
The research aims to design and create a payment bill validator application at the Palopo City State Treasury Service Office. This application is designed to facilitate KPPN staff in the process of channeling budgets to work units, as well as helping the process of validating accounts submitted by work units whether the account is valid or not. Data was collected through interviews, observations, and literature studies. The results showed that the developed application has a high level of usability, with an average score of 84% based on the System Usability Scale (SUS) assessment. This score falls into the “Very Feasible” category and indicates that the application is suitable for use. The application was also tested with whitebox testing techniques to ensure the program flow, logical structure, and procedures run well. The results of testing by users involved 30 respondents who gave an average rating of 84%, which is included in the “Very Good” category. This shows that the developed payment bill validator application has met user needs and is ready to be implemented at KPPN Palopo City.